Analysing crop combination patterns in the district of south Bihar, India - Sonam Kumari,; Prashant Kumar, (National Geographical Journal of India, 2025)
The study of crop combinations holds immense significance in agricultural geography. Crop combination refers to the aggregate of different crops cultivated within a specific region at a given time. This technique helps identify areas sharing a significant proportion of higher-ranked crops and is a necessary measure for analyzing cropping intensity. This research paper focuses on examining crop combination regions in the districts of South Bihar, aiming to highlight the significant variations in crop patterns across the study area. The study is based on secondary data for the agricultural year 2022-23. Weaver’s method of crop combination has been employed to compute and analyze the data. The findings reveal that most districts in South Bihar experienced a two-crop combination pattern. Among these, paddy and wheat emerged as the dominant crops, cultivated across different seasons throughout the region. This research provides valuable insights into the agricultural dynamics of South Bihar, helping policymakers and stakeholders understand regional cropping patterns and develop strategies for sustainable agricultural practices.